Investigating Orthopaedic Surgical Prophylaxis Changes and Post-operative Acute Kidney Injury (AKI) in NHS Grampian - a Test Case for NHS Scotland. (2017) - Marwick, Charis; Sneddon, Jacqui; Fletcher, Eilidh; Patton, Andrea; Bayne, Gwen
No abstract available